Journey to the Light:: Vipassana Meditation and Hesychastic Prayer - Nyunt, Moe Moe (Asia journal of theology, 2023)
This article is a comparative study of two orthodox religious practices: the Orthodox Buddhist practice of vipassana meditation and the Orthodox Christian practice of hesychastic prayer. The article acknowledges that both religions share the common idea of meditation/contemplation as an inner journey toward enlightenment. On the one hand, the Buddhist yogi is enlightened by observing the constantly changing nature of one’s mind-body relationship and hopes for being reborn as a deva or Brahma (god/celestial being). The Christian hesychast, on the other hand, is awakened by the Spirit of God in the deification (sharing divine likeness) process through contemplative prayer. The hesychast is enlightened by unifying his or her mind-heart with the trinitarian God. Both practices help to transform the practitioners to shine in this world. However, the deified hesychast lives in light of eternity.